Address by Irina Bokova, Director-General of UNESCO, on the occasion of the reception hosted by the Nordic Countries (Iceland, the Kingdom of Denmark, Finland, the Faroe Islands, the Kingdom of Norway and the Kingdom of Sweden); UNESCO, 5 November 2015 - UNESCO. Director-General, 2009-2017 (Bokova, I.G.) (5 Nov. 2015, 2015)
Electronic version only